DIAGNOSTIC ACCURACY OF SONOGRAPHIC MEASUREMENT OF THE LOWER UTERINE SEGMENT THICKNESS IN THIRD TRIMESTER IN PREDICTING THE OCCURRENCE OF UTERINE RUPTURE IN WOMEN WITH PRIOR CESAREAN SECTION (The Research of Medical Science Review, 2025)
OBJECTIVE: To determine the area under receiver operating curve analysis for lower uterine segment thickness in third trimester in predicting the occurrence of uterine rupture in women with prior cesarean section. STUDY DESIGN: Descriptive validation study PLACE AND DURATION OF STUDY: Department of Obstetrics & Gynaecology and Department of Radiology, Combined Military Hospital-Multan from 1st Oct 2024 to 30 March 2025. MATERIAL AND METHODS: In this descriptive validation study, 278 pregnant women with low-transverse cesarean scars who were between 30 and 36 weeks along participated. Evaluations of uterine scars, maternal data, and delivery outcomes were examined. Myometrial thickness and sonographic LUS were determined transvaginally and transabdominally. Clinical results were compared with LUS thickness's sensitivity and specificity for uterine rupture or dehiscence prediction. RESULTS: In this study, 278 women who had previously undergone cesarean sections had their diagnostic accuracy in predicting uterine rupture based on sonographic lower uterine segment (LUS) thickness assessed. With a cutoff of ≤2.25 mm, the overall diagnostic accuracy was 72.66%, the sensitivity was 71.25%, and the specificity was 73.23%. While mode of birth and LUS thickness were identified as important prognostic markers, no significant relationships were discovered with age, gestational age, or parity. CONCLUSIONS: Sonography improves uterine rupture risk assessment in patients who have had previous caesarean deliveries, allowing for safer treatment.